2013
DOI: 10.1259/dmfr.20120332
|View full text |Cite
|
Sign up to set email alerts
|

Enamel pearls in permanent dentition: case report and micro-CT evaluation

Abstract: Objectives: To investigate the frequency, position, number and morphology of enamel pearls (EPs) using micro-CT (mCT) and to report a case of an EP mimicking an endodonticperiodontic lesion. Methods: Cone beam CT (CBCT) was performed in a patient to evaluate a radio-opaque nodule observed on the left maxillary first molar during the radiographic examination. Additionally, 23 EPs were evaluated regarding frequency, position, number and morphology by means of mCT. The results were statistically compared using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…In contrast to this, some researchers observed a lower prevalence of enamel pearls (0.74%) using micro CT [11]. In our study enamel pearls were seen only on molar teeth not in premolar and anterior teeth, this was consistent with the findings of previous studies, which did not find enamel pearls in premolars [15], but found enamel pearls in 0.22% of premolars and without occurrence in incisors [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to this, some researchers observed a lower prevalence of enamel pearls (0.74%) using micro CT [11]. In our study enamel pearls were seen only on molar teeth not in premolar and anterior teeth, this was consistent with the findings of previous studies, which did not find enamel pearls in premolars [15], but found enamel pearls in 0.22% of premolars and without occurrence in incisors [12].…”
Section: Discussionsupporting
confidence: 90%
“…Previously, the prevalence of EP has been estimated in vivo and ex vivo in conventional radiographs, cone beam computed tomography (CBCT) and extracted teeth [11]. To the best of our knowledge, no studies were carried out to assess the prevalence of enamel pearls in Saudi Arabian population.…”
Section: Introductionmentioning
confidence: 99%
“…Köklerde görülen şekil anomalilerinden biri olan mine incileri, bağ dokusu ataçmanına girerek sadece hemidezmozal birleşime müsaade ettikleri için periodontitis nedeni olarak görülmüşlerdir. Ek olarak, bu tür oluşumların yapısı ve konumu, plağın mekanik olarak tutulmasına izin verir ve hem hastalar hem de hekimler tarafından etkili bir şekilde uzaklaştırılmasını engelleyerek periodontal hastalıklara yol açabilir 6,[8][9][10] .…”
Section: Gġrġġunclassified
“…Günümüze kadar mine incileri in vivo ve ex vivo olarak konvansiyonel radyografi 6,13,14 ve konik ışınlı bilgisayarlı tomografi (KIBT) 15,16 kullanılarak değerlendirilmiştir. Bununla birlikte son on yılda mikro-BT, diş sert dokularının üç boyutlu değerlendirilmesi için invaziv olmayan tekrarlanabilir bir yöntem 8,17 Tespit edilen mine incilerinin 1 tanesinin su damlası şeklinde, 10 tanesinin ise küre şeklinde olduğu görülmüştür. Küre şeklindeki incilerin çapları 0.3 mm ile 1.7 mm arasında değişiklik göstermektedir (ortalama 1.12 mm) (Tablo 3).…”
Section: Gġrġġunclassified